ETHNOSEMANTICS IN EVERYDAY SINGLISH - Aniroh, Kun (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2009)
Widely used in the world, English has grown to many varieties in which one of them is everyday Singlish. Singlish is a kind of English spoken by Singaporean com¬munities in informal situations. In everyday Singlish lexi¬cons not found in original English are ubiquitously used. The area of concern of etlinosemantics is the one with the appearance of the lexical semantics in a certain language. These lexicons have certain meanings, flavours and nu¬ances that make a language specific and unique. This is due to the fact that this specific lexicon use has a close connection with a particular culture and race. The study of eth¬noserr-antics in everyday Singlish shows that the unique¬ness is closely related with Singaporean cultures. There fore, the study of ethnosemanties which is explorable from local varieties will help understand the cultures, the charac¬teristics and the life of Singaporeans as a speech community.